Sanitary-hygienic control of two collective catering units in north of Portugal - Pereira, Ermelinda (2019)
The catering units provide food and beverages to kindergartens, schools, hospitals, etc., being extremely important to guarantee the quality and safety of the meals prepared on these units. The compliance of Prerequisite Programs regarding good hygiene practices, plans for cleaning and disinfection, equipment, infrastructures, among other issues, is obligatory. Some works have been done in order to identify weaknesses in food safety management systems by the evaluation of the knowledge and attitudes of food handlers (Garayoa et al., 2011; Pereira et al., 2015), and by microbiological quality of work surfaces, operators’ hands and meals (Petruzzelli et al., 2018).